Trajectories analysis of comorbid depression and anxiety among Israeli veterans: The implications on cognitive performance. (December 2022) - Aloni, Roy; Ginzburg, Karni; Solomon, Zahava
Abstract: Background: Among war veterans, research has indicated high rates of depression, anxiety, and comorbidity of these disorders, with even higher rates among prisoners-of-war. However, little is known about the longitudinal effects of comorbidity profiles on cognitive performance, particularly in the case of aging war veterans. Method: This longitudinal study focuses on Israeli veterans from the 1973 Yom Kippur War, with assessments at four time-points: 1991 (T1), 2003 (T2), 2008 (T3), and 2015 (T4). Two groups were included: veterans who were held captive (ex-POWs; n  = 196), and veterans who were not (war veterans; n  = 159). Participants completed validated self-report measures, and their cognitive performance was assessed using the Montreal Cognitive Assessment (MoCA). Results: Three distinct profiles of comorbidity were identified: resiliency (57.5%, n  = 204); delayed-onset (29.6%, n  = 105), and chronic (13.00%, n  = 46). The chronic profile identified mostly among ex-POW (91.3%, n  = 42), veterans with lower education at T1, and with more cognitively impaired compared to the other profiles (p < .0001). No differences were found between the profiles in age and family status at T1. Conclusions: The findings highlight the importance of viewing aging veterans as a high-risk population for cognitive impairments, particularly those suffering from chronic comorbidity of depression and anxiety. Therefore, the appropriate diagnosis and cognitive treatment are required to preserve cognitive abilities and prevent decline.